2022
DOI: 10.3390/polym14010191
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Dyeing of Wool Fabrics Using Selenium Nanoparticles

Abstract: This work aims to utilize selenium nanoparticles (Se-NPs) as a novel dyestuff, which endows wool fibers with an orange color because of their localized surface plasmon resonance. The color characteristics of dyed fibers were evaluated and analyzed. The color depth of the dyed fabrics under study was increased with the increase in Se content and dyeing temperature. The colored wool fabrics were characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDX) and an X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Moreover, SeNPs exhibited low cytotoxicity [ 15 , 24 ]. They have contributed to a variety of health-promoting activities and actions aimed at disease prevention and treatment [ 25 , 26 ] and have received considerable attention in the literature [ 15 , 16 , 27 , 28 , 29 , 30 , 31 ]. However, to the best of our knowledge, no study has been reported prior to our investigation of the utilization of SeNPs as antiviral agents for all types of fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SeNPs exhibited low cytotoxicity [ 15 , 24 ]. They have contributed to a variety of health-promoting activities and actions aimed at disease prevention and treatment [ 25 , 26 ] and have received considerable attention in the literature [ 15 , 16 , 27 , 28 , 29 , 30 , 31 ]. However, to the best of our knowledge, no study has been reported prior to our investigation of the utilization of SeNPs as antiviral agents for all types of fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis of Se-NPs Se-NPs were synthesized via redox reaction based on the procedure described by Abou Elmaaty et al 34 . Sodium hydrogen selenite was utilized, as a precursor for Se-NPs at different concentrations of 50 and 100 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Each measurement was recorded at different points of the samples. The contact angles and the free surface energy were determined as previously described [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…All dyed samples presented decreased values for interfacial tension with the biological fluids, which indicates a tendency towards increased biocompatibility (especially in the case of the P8 sample) when compared with the raw fabrics (Figure 14). SFE results from the interactions between the molecules that are present on the outer layer of the wool fibers, and provides information about how the fabrics will behave when coming into contact with the human body [25,42]. The data of an in vivo study evaluating the influence of SFE on fabrics made from cotton and polyester strongly suggest that thermal stress under dry and warm conditions was significantly reduced in subjects who wore clothes and shoes manufactured from fabrics with higher hydrophilic properties compared with the group who wore hydrophobic equipment [42].…”
Section: Contact Angle and Indirect Biocompatibilitymentioning
confidence: 99%